COMMUNITY EMPOWERMENT: IMPROVING PRODUCT QUALITY AND COMMUNITY WELFARE - Pratama, R.Lian Nando; Mukmin, Hasan; Yanti, Fitri (Universitas Islam Negeri Raden Intan Lampung, 2023)
Micro, small, and medium enterprises (MSMEs) have an essential role in Indonesia's economy and poverty alleviation. The obstacle MSMEs face today is the lack of innovation in access to technology, marketing capital, and management. One of the advantages of the village is that it has a professional community, but this cannot be separated from the extension of the village government to improve the quality of community management by empowering the skills of the village community. This study aims to reveal community empowerment activities to enhance product quality and welfare through the Siger Bori Joint Business Group (KUBE) in Labuhan Ratu Village, Kedaton District, and Bandar Lampung City. The type of research used is field research with a qualitative, descriptive approach. Data is sourced from primary and secondary sources, with data collection techniques, interviews, observations, documentation, and data analysis including data education, data presentation, data validity, and conclusions. The technique of testing the data's reality is a triangulation technique. The study results showed that Bori's empowerment activities began with activity socialization, training, coaching, and mentoring stages. After the training program for KUBE Siger Bori members, developments and changes began to be seen in the quality of already better products. In addition, there is a change in the increase in income in the family. The income earned can be used to meet his family's needs.